2021
DOI: 10.1021/acs.macromol.1c01706
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Two Distinct Formation Pathways of the Thermodynamically Stable Phase to Tune Crystal Polymorphism: The Case of Butene/Pentene Copolymers

Abstract: Macromolecules with unique long-chain architecture can not only crystallize into a thermodynamically stable crystal but also form a kinetically favored crystal, where the latter may subsequently transform into the former to further lower the free energy. Therefore, to obtain the thermodynamically stable crystal, there are in principle two distinct formation pathways including the direct crystallization from the amorphous melt and the indirect phase transition from the initially generated modification, of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Figure 2 shows that all the freeze-dried samples present strong scatterings at q = 7.1, 12.3, and 14.4 nm −1 , assigning to the (110), (300), and (220 + 211) lattice planes of form I′ or I. 18 Figure 3 shows the DSC curves of freeze-dried PB-1 collected upon heating at different rates (1−20 °C/min). All the freeze-dried samples with different MWs but the same c (FD-5) exhibit two melting regions at 85−100 °C and 110−125 °C upon heating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows that all the freeze-dried samples present strong scatterings at q = 7.1, 12.3, and 14.4 nm −1 , assigning to the (110), (300), and (220 + 211) lattice planes of form I′ or I. 18 Figure 3 shows the DSC curves of freeze-dried PB-1 collected upon heating at different rates (1−20 °C/min). All the freeze-dried samples with different MWs but the same c (FD-5) exhibit two melting regions at 85−100 °C and 110−125 °C upon heating.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the facility of processing and the better stability of end-use products, it is highly desired to directly obtain form I′ in melt processing without passing through the intermediate form II phase. Typical methods developed to directly obtain form I′ include self-seeding, nanoscale confinement, copolymerization, and CO 2 treatment . Nevertheless, form I′ is unstable at high temperatures and may transform back into form II (designated as I′-to-II transition) upon further heating or stretching through a melt-recrystallization pathway. , This thermally induced phase transition can impact the thermal stability and thermomechanical properties of form-I′ PB-1 materials used at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1‐butene copolymers incorporated with linear α‐olefin co‐monomers, the relatively small co‐units (including ethylene, propylene, and 1‐pentene) effectively accelerate the kinetics of phase transition, whereas the longer co‐units with more than 5 carbon atoms greatly slow down the process of phase transition. [ 45‐50 ] Zheng et al . [ 51 ] synthesized 1‐butene/4‐methyl‐1‐pentene copolymers to investigate the influence of branched co‐units on phase transition behaviors.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…It has been reported that lots of factors would affect the phase transition kinetics, such as the blending with other polymers, [25][26][27][28] copolymerization, [29][30][31][32][33][34] molecular weight, [35][36][37] temperature, 13,38,39 pressure, 40,41 extension, 11,12,42,43 nanofillers, [44][45][46] crystallization conditions, [47][48][49][50][51][52] and so on. Among all these factors, adding nanofillers and changing the crystallization conditions of form II are of significant value which can be used in the practical processing process to promote the phase transition process.…”
Section: Introductionmentioning
confidence: 99%